Efficacy assessment of treatment of patients with stage III primary open-angle glaucoma using a combined method (phosphene electrical stimulation and photomyostimulation) (Ukrainian Journal of Ophthalmology, 2026)
The purpose: to assess the efficacy of a combined method, including phosphene electric stimulation (FES) and photomyostimulation, in treatment of patients with stage III primary open-angle glaucoma (POAG) with compensated IOP. Material and Methods. Twenty-two eyes (22 patients) with stage III POAG with drug-compensated IOP were studied. The combined method consisted of a 10-minute FES session and a 10-minute photomyostimulation session. A patient had a 20-minute rest between the sessions. The treatment course included the10 sessions. To perform the FES session, a current value was specified in each certain case depending on a baseline phosphene threshold of electric sensivity (PTES). Photostimulation was carried out with impulse movement frequency (IMF), optimal to a patient, in a chaotic mode under scotopic conditions.Results. The treatment resulted in the improvement of the functional mobility of the oculomotor system (the values of the IMX index significantly increased in all three modes). The functional activity of the visual system increased: PTES decreased by 21.4%, PhCFFF in the 1.5 and 3.0 modes increased by 21.6% and 18.1%, respectively. The mean deviation of light sensitivity decreased by 14.6% and the mean retinal light sensitivity according to all MS threshold values increased by 17.9 % with enlarged summarized visual field by14.8%. The method proposed had a positive effect for ocular hemodynamics. Thus, the facility of aqueous outflow increased by 29.4%, the Ро/С coefficient decreased by 27.1% and the rate of aqueous flow increased by 31.1%Conclusion. The proposed method of treatment can be included in the complex of curative measures for the patients with stage III POAG in order to increase the functional activity of the visual system and to improve the patients’ quality of life.
Keywords: primary open-angle glaucoma; treatment; phosphene electric stimulation; photomyostimulation